OPTIMIZING INTRADIALYTIC NUTRITIONAL INTAKE: A SYSTEMATIC REVIEW OF SAFETY AND CLINICAL EFFECTS DURING HEMODIALYSIS - Setiowati, Tutut; Yulian, Vinami; Sugiharto, Sugiharto (Universitas Muhammadiyah Ponorogo, 2025)
Hemodialysis is an essential therapy for patients with end-stage kidney disease; however, it is often accompanied by the risk of malnutrition, which contributes to reduced quality of life and increased mortality. Intradialytic eating (IDE) has the potential to offer clinical benefits for hemodialysis patients, but its practice remains controversial, particularly regarding safety and possible clinical outcomes. This study aims to evaluate the safety and clinical impact of IDE through a systematic review of the available scientific evidence. A comprehensive literature search was conducted using PubMed, Cochrane CENTRAL, ScienceDirect, EBSCO, and Scopus databases. Studies were selected based on relevance to the PICO framework. A total of 9,142 articles were identified, and after data screening and extraction, eight studies met the inclusion criteria. The findings suggest that intradialytic eating (IDE) has the potential to improve nutritional status and quality of life in hemodialysis patients at risk of malnutrition, although it still carries the risk of hypotension and blood pressure instability. Safe and effective implementation of IDE requires careful patient selection based on hemodynamic stability, provision of high-protein and low-electrolyte foods, administration during the mid-to-late phase of dialysis, and close clinical monitoring. Multidisciplinary team involvement and supportive health service policies are crucial for the long-term success of IDE practices.